1995
DOI: 10.1159/000201246
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A Reduces the Severity of Cold-Restraint-Induced Gastric Lesions: Role of Leukocytes

Abstract: The objective of this study was to determine the role of cyclosporin A (CsA) on cold-restraint-induced gastric lesions. Animals were subjected to 3 h immobilization at 4 ° C in plastic restraining devices following a starvation period of 48 h. Gastric samples were obtained for the measurement of myeloperoxidase (MPO) activity, an index of number of peroxidase positive cells and thiobarbituric acid-reactive substances (TBARS; lipid peroxidation). Animals were pre-treated with CsA which is a potent immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In vivo research in the cat mesentery, hamster skin, and rat ear showed that hypoperfusion during ischemia enhanced the adhesion of leukocytes to the vascular endothelium [6,22]. Polymorphonuclear leukocytes (PMNs) have been implicated in the pathogenesis of stress ulcers by many investigators [23,24]. We observed that inhibition of NO synthesis increased PMN infiltration and enhanced gastric mucosal dysfunction in hemorrhagic stress-induced ulcers.…”
Section: Discussionmentioning
confidence: 78%
“…In vivo research in the cat mesentery, hamster skin, and rat ear showed that hypoperfusion during ischemia enhanced the adhesion of leukocytes to the vascular endothelium [6,22]. Polymorphonuclear leukocytes (PMNs) have been implicated in the pathogenesis of stress ulcers by many investigators [23,24]. We observed that inhibition of NO synthesis increased PMN infiltration and enhanced gastric mucosal dysfunction in hemorrhagic stress-induced ulcers.…”
Section: Discussionmentioning
confidence: 78%
“…The stress ulcer model stimulates the production of oxygen-derived free radicals (in endothelial cells and polymorphonuclear neutrophiles) which cause gastric mucosal tissue damage by inducing ischemia at the level of gastric microvasculature, and the direct role of the oxygen free radicals in the etiopathology of acute stress ulcers has been established (Coskun et al 1995, Ohara et al 1990Manicelli et al 1990). It is well known that the exposure of gastric mucosa to damaging factors such as water immersion/restraint stress and NSAIDs produce acute ulcers that are mainly mediated by ROS (Carnevale et al 2011), and gastric protection against absolute ethanol injury in rats has been linked to antioxidant activity (de-Faria et al 2012) .…”
Section: Discussionmentioning
confidence: 99%
“…Following 12 hours of food (but not water) deprivation, test rats were given the extract (100 and 200 mg/kg) by oral route while control rats received the vehicle. One hour later, the rats were placed in small individual wire cages and immersed in cold water (3)(4)(5) o C), up to the level of the xiphoid. 120, minutes later blood samples were taken and the animals were sacrificed using ether and the stomachs removed for the assessment of lesion formation and mucus production (lesion indices expressed as the sum of the lengths of the lesions for each rat).…”
Section: Cold Stress-induced Gastric Lesionsmentioning
confidence: 99%
“…Recent studies suggest that toxic oxygen molecules might be one of the important factors in inducing gastric mucosal injury during cold‐restraint stress and the increase of xanthine oxidase activity might be responsible for the production of oxygen free radicals. 1,2,15 Lipid peroxidation, which results from the generation of reactive oxygen species, was suggested to be closely related to production of the gastric damage by cold‐restraint stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that oxygen free radicals might be one of the important factors in inducing gastric mucosal injury during stress. 1,2,15…”
mentioning
confidence: 99%